Plasmaspheric Plumes and EMIC Rising Tone Emissions. Issue 11 (28th November 2018) - Grison, B.; Hanzelka, M.; Breuillard, H.; Darrouzet, F.; Santolík, O.; Cornilleau‐Wehrlin, N.; Dandouras, I.
Abstract: Due to its polar orbit Cluster spacecraft crossed plasmaspheric plumes out of the magnetic equatorial plane. We study the occurrence of broadband, narrowband, and rising tone emissions in the plume vicinity, below the local proton gyrofrequency. Based on a database of 935 Cluster plumes crossings, reduced to 189 unique plumes, we find that broadband activity is the most common case. We confirm result from a previous study showing that plume vicinity is not a preferred place for observing narrowband emissions. Rising tones are the less frequently observed of these three kinds of emissions. Nevertheless, ElectroMagnetic Ion Cyclotron (EMIC) rising tone occurrence rate is high compared to the narrowband one: Tones are seen in six of 30 plume events (20%) when narrowband emissions are observed. Rising tones are observed at absolute magnetic latitudes larger than 17° and up to 35° . We detail the 16 August 2005 plume crossing when a rising tone is observed. Results of a ray tracing analysis agree with a tone triggering process taking place above 15° of magnetic latitude. Key Points: Coherent rising tones are found in 20% (6/30) of the plume (and vicinity) events with EMIC emissions EMIC rising tones are observed at magnetic latitudes larger than 17 degrees and up to 35 degrees Emissions below H + gyrofrequency in the vicinity of plasmaspheric plumes are mainly broadband